Biotechnology for biofuel production and optimization - Eckert, Carrie A.; Trinh, Cong T. (Elsevier, 2016)
Biotechnology for Biofuel Production and Optimization is the compilation of current research findings that cover the entire process of biofuels production from manipulation of genes and pathways to organisms and renewable feedstocks for efficient biofuel production as well as different cultivation techniques and process scale-up considerations. This book captures recent breakthroughs in the interdisciplinary areas of systems and synthetic biology, metabolic engineering, and bioprocess engineering for renewable, cleaner sources of energy.
Biotechnology for Biofuel Production and Optimization Preface 1. Engineering Central Metabolism for Production of Higher Alcohol-based Biofuels 2. Secondary metabolism for isoprenoid-based biofuels 3. Metabolic engineering for fatty acid, biodiesel production 4. Pathway and strain design for biofuels production 5. RNA-based molecular sensors for biosynthetic pathway design, evolution, and optimization 6. Pathway Assembly and Optimization 7. Design of Dynamic Pathways 8. Applications of Constraint-Based Models for Biochemical Production 9. Biotechnological strategies for advanced biofuels production: enhancing tolerance phenotypes through genome-scale modifications 10. Evolutionary Methods for Improving Production of Biorenewable Fuels and Chemicals 11. Biomass utilization 12. Ralstonia eutropha H16 as a platform for the production of biofuels, biodegradable plastics, and fine chemicals from diverse carbon resources 13. Methane Biocatalysis: Selecting the Right Strain 14. Photosynthetic Platform Strain Selection: Strain Selection Considerations and Large Scale Production Limitations 15. Interpreting and designing microbial communities, from components to interactions to emergent properties 16. Cell-free biotransformation 17. Microbial Electrochemical Cells and Biorefinery Energy Efficiency 18. PhotoBioHybrid Solar Conversion with Metalloenzymes and Photosynthetic Reaction Centers 19. Photobioreactors 20. Scale-up Considerations for Biofuels.
Keywords: Biomass energy.; Biomass energy -- Environmental aspects.; Biotechnology.; elektronické knihy; electronic books